Arterial Stiffness and Endothelial Function in Obese Children and Adolescents and Its Relationship with Cardiovascular Risk Factors - Joo Turoni, Claudio Martín (2013)
Background: Obesity is related to an increase in the rates of cardiovascular disease. Objective: To establish the impact of obesity on vascular function (endothelial function and arterial stiffness) in children and adolescents and its relationship to cardiovascular risk factors. Methods: In obese (OB) children and adolescents, endothelial function and arterial stiffness were evaluated by a pulse plethysmography method (reactive hyperemia and index of digital volume waveforms, respectively). Data were compared with the non-obese (non-OB) group (body mass index >10th to <97th percentile). Anthropometric parameters, body fat percentage, fasting glucose, lipid profile, insulinemia, HOMA-IR and hemodynamic parameters were determined in both groups. Results: Body mass index, weight, waist circumference, body fat, insulinemia and HOMA-IR were significantly higher in the OB group. The OB group showed impaired endothelial function (15.8 ± 0.2%, n = 37) compared to the non-OB group (41.4 ± 5%, n = 20; p < 0.001) and increased arterial stiffness. Endothelial function was only negatively correlated with waist circumference and HOMA-IR in the OB group, whereas a positive correlation was found between insulinemia and HOMA-IR. Conclusions: This study shows that impaired vascular function is already present in OB children and adolescents. The fact that obesity is associated with some markers of cardiovascular risk suggests the importance of early lifestyle interventions in this population to prevent cardiovascular disease.